Crustacea Brachyura Morphology And Morphometrically in Buloh Beach Intertidal Zone, Minahasa District, North Sulawesi - Jumeini, Jumeini; Paransa, Darus S. J.; Schaduw, Joshian N. W.; Mantiri, Desy M. H.; Pelle, Wilmy E.; Manu, Gaspar D. (Jurnal Ilmiah Platax, 2022)
Brachyura crabs, especially coastal crabs, live in the intertidal zone with zone shape sandy beaches, muddy beaches, and rocky beaches. The colors on the crabâ€™s carapace are caused by the presence of carotenoid pigments. The purpose of the study was to identify crabs morphologically and morphometrically. The sampling location was in Buloh Beach, Tateli Weru Village, Mandolang District, Minahasa Regency, North Sulawesi Province. Sampling using the cruise method, which is a research activity carried out by tracing the coastal area at the lowest tide by capturing organisms as samples directly. The crab samples found then morphologically identified by observing the color and shape of the carapace, claws, walking legs, presence of spines on the carapace, carapace size, abdomen shape, the characteristics of the leg organs presence of hair (setae), and morphometric calculations were also carried out. Based on the morphology of the crabs found, namely: Grapsus albolineatus (Latreille in Milbert, 1812), Atergatis floridus (Linnaeus, 1767), Pilumnus vespertilio (Fabricius, 1793), and Uca (Galasimus) tetragonon (Herbst, 1790)Keywords: Buloh Beach; Brachyura; Morphology; morphometrically; DiversityAbstrakKepiting brachyura khususnya kepiting pesisir hidup di zona intertidal dengan bentuk zona pantai berpasir, pantai berlumpur dan pantai berbatu. warna-warna pada karapas kepiting disebabkan karena adanya kandungan pigmen karotenoid. Tujuan penelitian untuk mengidentifikasi kepiting secara morfologi dan morfometrik. Lokasi pengambilan sampel di Pantai Buloh, Desa Tateli Weru, Kecamatan Mandolang, Kabupaten Minahasa, Provinsi Sulawesi Utara. Pengambilan sampel menggunakan metode jelajah (cruise methods) yaitu suatu kegiatan penelitian dilakukan dengan menelusuri daerah pesisir pantai saat surut terendah dengan menangkap organisme sebagai sampel secara langsung. Sampel kepiting yang ditemukan kemudian dilakukan identifikasi morfologi dengan memperhatikan warna dan bentuk karapas, capit, kaki jalan, keberadaan duri pada karapas, ukuran karapas, bentuk abdomen dan ciri-ciri organ kakinya seperti keberadaan rambut (setae), serta dilakukan perhitungan morfometrik. Berdasarkan identifikasi morfologi kepiting yang ditemukan, yaitu: Grapsus albolineatus (Latreille in Milbert, 1812), Atergatis floridus (Linnaeus, 1767), Pilumnus vespertilio (Fabricius, 1793), danÂ  Uca (Galasimus) tetragonon (Herbst, 1790).Kata kunci : Pantai Buloh; Brachyura; Morfologi; Morfometrik; Keanekaragaman